Optical limiting behavior of ring substituted zinc, indium and gallium phthalocyanines in the presence of quantum dots - Britton, Jonathan; Litwinski, Christian; Durmuş, Mahmut; Chauke, Vongani; Nyokong, Tebello (World Scientific Publ Co Pte Ltd, 2011)
This paper presents the study of the effects of CdTe-TGA quantum dots (QDs) on optical limiting ability of different phthalocyanine (Pc) complexes (1-10) containing Zn, Ga, In central metals and substituted with benzyloxyphenoxy, phenoxy, tert-butylphenoxy and amino groups. The optical limiting parameters of Pcs were higher for tert-butylphenoxy when compared to benzyloxyphenoxy and phenoxy substituents, in DMSO. Non-peripheral substitution decreased the optical limiting parameters. Third-order susceptibility (Im[chi((3))]/alpha)values of Pcs in the absence and presence of CdTe QDs were in the 10(-12) to 10(-10) esu.cm range. Hyperpolarizabilities (gamma) ranged from 10(-31) to 10(-29) esu L for Pc alone or in mixture with QDs. There is a general improvement in optical limiting ability of Pc complexes in the presence of CdTe TGA QDs. Due to these promising results, future work can be implemented for the creation of Pc:QD thin films, which would then be examined to ensure that their optical limiting ability is still acceptable.
Keywords: quantum dots; phthalocyanine; optical limiting; hyperpolarizabilities; third order susceptibility